2008
DOI: 10.4161/psb.3.8.6359
|View full text |Cite
|
Sign up to set email alerts
|

Plant polyphenols in cell-cell interaction and communication

Abstract: Plant polyphenols including flavonoids and tannins are important constituent of our everyday diet and medical herbals. It is broadly accepted that polyphenols may protect us from toxins, carcinogens and pollutants though the mechanisms of the polyphenols action is still not clear. Here we discuss the ability of polyphenols and especially gallate rich compounds like tannins and catechin gallates to interact with proteins and lipids, establish binding between adjacent bilayer surfaces and initiate membrane aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 31 publications
(35 reference statements)
1
24
0
1
Order By: Relevance
“…For hydrolysable tannins, increasing fluidity in the internal region of the lipid bilayer has been shown, but no changes were found on the surface of the membrane of the Chinese hamster cell line B14 [50]. It is known that the binding of tannins to the membrane surface of cells may induce cluster and raft formation [34]. It may prevent erythrocytes swelling and release of hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For hydrolysable tannins, increasing fluidity in the internal region of the lipid bilayer has been shown, but no changes were found on the surface of the membrane of the Chinese hamster cell line B14 [50]. It is known that the binding of tannins to the membrane surface of cells may induce cluster and raft formation [34]. It may prevent erythrocytes swelling and release of hemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are data showing that erythrocytes bind polyphenols and may increase the capacity of blood to scavenge oxidants. It has been shown that polymerized polyphenols are bound by proteins on the cell surface rather than intracellular structures and that erythrocyte-polyphenol complexes may serve as potent "sinks" for RONS [34][35][36]. We used HClO and ONOO -as oxidants that can also be transformed into other radicals, which can lead to different damage of biomolecules.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their low bioavailability, these compounds can act as signaling molecules that can induce endogenous antioxidant defense pathways as well as modulate many intracellular signaling processes associated with oxidative stress and inflammation. In that regard, the health-promoting benefits of polyphenol parent compounds and their microbial metabolites have been related to translocation into the nucleus of nuclear factor erythroid 2-related factor 2 (Nrf2) and induction of Nrf2-antioxidant response element signaling pathway [7], suppression of nuclear factor κB (NF-κB) and activator protein 1 (AP-1) [8], induction of glutathione conjugates [9] and glutathione S-transferase [10], caspase-3 activation [11], c-jun NH 2 -terminal kinase [12] and P38 activation [13], and modulation of mitogenactivated protein kinases [14] and the phosphoinositide-3 kinase/Akt protein kinase B pathway [15].…”
Section: Role Of Polyphenols In Other Diseases and Possibly Cfmentioning
confidence: 99%
“…2 suggested that genistein could alter the aggregation nature of milk peptides by interfering with the electrostatic and hydrophobic interactions of peptide macroaggregates. The interactions within the associated aggregates may be due to the ionic interactions between the p electrons in the phenol ring of genistein and the NH 3 þ group of amino acid side chains (Tarahovsky, 2008).…”
Section: Effect Of Solution Ph and Genistein On Aggregation Of Milk Pmentioning
confidence: 99%